MICROSTRUCTURE AND WEAR PROPERTIES OF FeCrC, FeW AND FeTi MODIFIED IRON BASED ALLOY COATING DEPOSITED BY PTA PROCESS ON AISI 430 STEEL - Teker, T.; Karatas, S.; Yilmaz, S. O. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2014)
The plasma transferred arc (PTA) process was used for developing wear resistance of AISI 430 steel substrate. Appropriate quantities of FeCrC, FeW and FeTi powders were combined to create conditions that synthesized M7C3 particles into reinforced Fe-based composite surface coating. The phase transformations on new created coated surfaces were comprehensively examined by using a combination of scanning electron microscopy (SEM), microanalysis by energy dispersive spectrometry (EDS), X-Ray diffraction (XRD), microhardness and abrasive wear tests. The microstructure studies of the superficial layers of the coating revealed presence of a mixture of the dendritic phase structure of austenite (gamma) and fine eutectic M7C3 carbides. The results show that; the concentrations of the elements (Cr, W, Ti) added as ferroalloys, the size of dendrites formed in the coated surface, the change of hardness of the coated surfaces, the carbide volume rate and thickness of the coating changed by the variation of the processing parameters (ratio of reinforcement particulates and heat input).
Keywords: PTA; AISI 430; Surface Coating